2013
DOI: 10.1585/pfr.8.1402134
|View full text |Cite
|
Sign up to set email alerts
|

Improved Three-Dimensional CCS Method Analysis for the Reconstruction of the Peripheral Magnetic Field Structure in a Finite Beta Helical Plasma

Abstract: In the previous 3D Cauchy-condition surface (CCS) method analysis to reconstruct the magnetic field profile in the Large Helical Device (LHD), one assumed an impractically large number of magnetic sensors, i.e., 440 field sensors and 126 flux loops. In the singular value decomposition (SVD) process employed in the CCS method, a gap is found in the magnitude of the singular values. The most accurate field results can be obtained if all the singular values smaller than the gap threshold are eliminated, independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The preliminarily unknown eddy current distribution in the vacuum vessel is reconstructed in a reversed field pinch device based on the external magnetic sensor signals [6]. Furthermore, the CCS method has been expanded to reconstruct the 3D magnetic field profile outside the non-axisymmetric plasma in the Large Helical Device (LHD) [7].…”
Section: Reconstruction Of the Plasma Surface Using The Ccs Methodsmentioning
confidence: 99%
“…The preliminarily unknown eddy current distribution in the vacuum vessel is reconstructed in a reversed field pinch device based on the external magnetic sensor signals [6]. Furthermore, the CCS method has been expanded to reconstruct the 3D magnetic field profile outside the non-axisymmetric plasma in the Large Helical Device (LHD) [7].…”
Section: Reconstruction Of the Plasma Surface Using The Ccs Methodsmentioning
confidence: 99%
“…The acquisition of the plasma shape has abundant and thorough research with profiles. Itagaki, Masafumi et al [7,8] found an effective way to reconstruct the 3D magnetic field profile outside the non-axisymmetric plasma in a reactor and indicated the plasma boundary precisely. However, they did not build a 3D model but visualized the result with profiles of the magnetic field.…”
Section: Related Workmentioning
confidence: 99%
“…Such information should be deduced from signals of magnetic sensors located near the vacuum vessel wall, since the direct measurement of physical quantities inside the plasma is usually difficult. The Cauchy condition surface (CCS) method [16][17][18][19][20][21][22][23] is one such idea for reconstructing the magnetic flux profile outside the plasma and hence the plasma boundary shape. The method has already been established for operating control and diagnosis of JT-60U [16], a tokamak-type device.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the method has been expanded to other devices such as KSTAR [17], JT-60SA [18] and QUEST [19]. Further, Itagaki et al developed the 3D CCS method [20][21][22] to reconstruct 3D magnetic field profile outside the non-axisymmetric plasma in the LHD. In these methods, the CCS, where both the Dirichlet and the Neumann conditions are unknown, is hypothetically placed in a domain that can be supposed to be inside the plasma.…”
Section: Introductionmentioning
confidence: 99%